Physiological and psychometric variables for monitoring recovery during tapering for major competition - Hooper, S. L.; MacKinnon, T.; Howard, A. (Medicine & Science in Sports & Exercise, 1999)
changes in plasma norepinephrine concentration, heart rate after maximal effort swimming and confusion as measured by the Profile of Mood States (POMS) predicted the change in swimming time with tapering (r2 = 0.98); the change in plasma norepinephrine concentration predicted the change in swim time with tapering (r2 = 0.82) by itself.